2022
DOI: 10.18814/epiiugs/2021/021013
|View full text |Cite
|
Sign up to set email alerts
|

Emplacement timing, temperature, and redox conditions of the Kambélé auriferous pluton, Batouri gold District, SE Cameroon

Abstract: The Kambélé auriferous pluton in south-eastern Cameroon is within the Central African Fold Belt (CAFB). New zircon LA-ICP-MS U-Pb ages, REEs patterns, zircon Ce 4+ / Ce 3+ ratios, and Ti-in-zircon thermometry, have been used to decipher the timing of mineralisation, redox conditions and emplacement temperature of the pluton. Cathodoluminescence images of 12 representative zircon grains from the Kambélé pluton reveal two types of zircon grains: type 1 grains are characterized by dark cores, serrated margins and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Zircon U-Pb age data revealed that granitoid intrusions were emplaced within an age bracket of ca. 670-620 Ma [20,27,57,58], with an average mean age of ca. 635 Ma obtained on syn-tectonic granitoid in the Bétaré Oya gold district [27], south of the present study.…”
Section: Local Geology Of the Lom Basinmentioning
confidence: 99%
See 1 more Smart Citation
“…Zircon U-Pb age data revealed that granitoid intrusions were emplaced within an age bracket of ca. 670-620 Ma [20,27,57,58], with an average mean age of ca. 635 Ma obtained on syn-tectonic granitoid in the Bétaré Oya gold district [27], south of the present study.…”
Section: Local Geology Of the Lom Basinmentioning
confidence: 99%
“…Such high δ 11 B values suggest the involvement of an I-type granitic pluton [73]. Neoproterozoic granitoids in the eastern Cameroon goldfields are also I-type metaluminous to slightly peraluminous and associated with gold mineralization [57,58]. As an incompatible element, B is readily transported by granitic melts and hydrous fluids derived therefrom [74].…”
Section: The Tourmaline-primary Gold Link and Ore-forming Fluidmentioning
confidence: 99%